Testes bioquímicos para avaliação do vigor em sementes de Mimosa caesalpiniaefolia Benth - Avelino, Mirella Carvalho Souza (2014)
Mimosa caesalpiniaefolia Benth. is a forest species of the Mimosaceae family, recommended for recovery of degraded areas. The evaluation of vigor by biochemical tests have been an important tool in the control of seed quality programs, and the electrical conductivity and potassium leaching the most efficient in the verifying the physiological potential. The objective, therefore, to adjust the methodology of the electrical conductivity test for seeds of M. caesalpiniaefolia, for then compare the efficiency of this test with the potassium in the evaluation of seed vigor of different lots of seeds M. caesalpiniaefolia. To test the adequacy of the electrical conductivity were used different combinations of temperatures , 25 °C and 30 ºC, number of seeds , 25 and 50, periods of imbibition , 4 , 8 , 12 , 16 and 24 hours , and volumes deionized water, 50 mL and 75mL. For potassium leaching test, which was conducted from the results achieved by the methodology of the adequacy of the electrical conductivity test, to compare the efficiency of both tests , in the classification of seeds at different levels of vigor, and the period 4 hours also evaluated because the potassium leaching test can be more efficient in the shortest time . The best combination obtained in experiment of electrical conductivity is 25 seeds soaked in 50 mL deionized or distilled water for 8 hours at a temperature of 30 ° C. Data were subjected to analysis of variance, the means were compared with each other by F tests and Tukey at 5 % probability, and when necessary polynomial regression analysis was performed. The electrical conductivity test performed at period eight hour proved to be more efficient in the separation of seed lots M. caesalpiniaefolia at different levels of vigor compared to the potassium test